Analisis Kemampuan Komunikasi Matematis Siswa Dengan Gaya Belajar Kompetitif - Purwati, Heni; Wuri, Dhian Endah (Pendidikan Matematika Universitas PGRI Yogyakarta, 2017)
The purpose of this study is to analyze the communication skills of students of SMP Eka Sakti Semarang who have a competitive learning style. The type of research is descriptive qualitative. Data collection techniques using test methods and interviews. The subjects consist of 2 grade VII students who have a competitive learning style. The data validity technique uses source triangulation. The results showed that both subjects showed the same mathematical communication ability indicators: 1) were less able to express mathematical ideas through oral, written, and demonstrated and visualized; 2) able to understand, interpret and evaluate mathematical ideas either orally, or in visual form; and 3) able to use terms - mathematical notations through oral, written, and interpreting and visualizing. These results show that they understand the problems faced but are not accustomed to writing them coherently, this is due to the aggressiveness of students with competitive learning styles more motivate them to complete the job quickly and correctly rather than following the procedure.Â Keywords: mathematical communication, learning style